Written Verb Naming Improves After tDCS Over the Left IFG in Primary Progressive Aphasia - Fenner, Amberlynn S.; Webster, Kimberly T.; Ficek, Bronte N.; Frangakis, Constantine E.; Tsapkini, Kyrana (Frontiers in Psychology, 2019)
Transcranial direct current stimulation (tDCS), a non-invasive neuromodulation technique, is an effective adjunct to naming treatments in post-stroke aphasia and primary progressive aphasia (PPA). Enhanced performance in oral and written naming and spelling of nouns with tDCS has been quantified in detail, but it is not known whether it is effective for verb treatment in PPA. We addressed the question of whether performance in naming and spelling of verbs can be augmented with anodal tDCS over the left inferior frontal gyrus (IFG). We compared tDCS coupled with oral and written verb naming + spelling treatment with oral and written verb naming + spelling treatment alone. In a double-blind, sham-controlled, crossover design, 11 participants with logopenic or nonfluent variant PPA received approximately 15 consecutive sessions of anodal tDCS and sham over the left IFG coupled with oral and written verb-naming + spelling treatment. Written verb-naming performance improved significantly more for trained verbs in the tDCS than the sham condition. Importantly, tDCS effects generalized to untrained items for written verb naming and were significant even at two months post-treatment. We conclude that tDCS over the left IFG can improve written verb naming and spelling in PPA.